Design and Construction of Portable CRISPR-Cpf1-Mediated Genome Editing in Bacillus subtilis 168 Oriented Toward Multiple Utilities - Hao, Wenliang; Suo, Feiya; Lin, Qiao; Chen, Qiaoqing; Zhou, Li; Liu, Zhongmei; Cui, Wenjing; Zhou, Zhemin (Frontiers in Bioengineering and Biotechnology, 2020)
Bacillus subtilis is an important Gram-positive bacterium for industrial biotechnology, which has been widely used to produce diverse high-value added chemicals and industrially and pharmaceutically relevant proteins. Robust and versatile toolkits for genome editing in B. subtilis are highly demanding to design higher version chassis. Although the Streptococcus pyogenes (Sp) CRISPR-Cas9 has been extensively adapted for genome engineering of multiple bacteria, it has many defects, such as higher molecular weight which leads to higher carrier load, low deletion efficiency and complexity of sgRNA construction for multiplex genome editing. Here, we designed a CRISPR-Cpf1-based toolkit employing a type V Cas protein, Cpf1 from Francisella novicida. Using this platform, we precisely deleted single gene and gene cluster in B. subtilis with high editing efficiency, such as sacA, ganA, ligD＆ligV and bac operon. Especially, an extremely large gene cluster of 38 kb in B. subtilis genome was accurately deleted from the genome without introducing any unexpected mutations. Meanwhile, the synthetic platform was further upgraded to a version for multiplex genome editing, upon which two genes sacA and aprE were precisely and efficiently deleted using only one plasmid harboring two targeting sequences. In addition, we successfully inserted foreign genes into the genome of the chassis using the CRISPR-Cpf1 platform. Our work highlighted the availability of CRISPR-Cpf1 to gene manipulation in B. subtilis, including the flexible deletion of a single gene and multiple genes or a gene cluster, and gene knock-in. The designed genome-editing platform was easily and broadly applicable to other microorganisms. The novel platforms we constructed in this study provide a promising tool for efficient genome editing in diverse bacteria.